(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In judicial practice, the correct identification and assessment of the objective side of the composition of the crime is one of the most important stages of the legal, fair and reasonable resolution of criminal cases. Because it is the objective side that determines the appearance of the crime, through which a conclusion is drawn about the commission or non-commission of the crime. The signs inherent in the objective side - action (or inaction), consequence and the causal connection between them - are the main elements proving the existence of the crime.